RESIDENTS SUPPORT TOWARDS CULTURAL HERITAGE TOURISM: THE RELEVANCE OF HERITAGE PROXIMITY AND TOURISM PERCEIVED IMPACTS - Ahmed, Nassar (Revista de turism - studii și cercetări în turism, 2023)
Abstract For tourism to grow sustainably, it is crucial to comprehend communities' opinions regarding tourism's consequences, along with the degree with which they support the growth of tourism in their particular regions. Despite the numerous factors investigated as the predictors of locals' attitudes toward tourism, researchers have yet to confirm whether heritage proximity is applicable in predicting the different domains of tourism “economic, socio-cultural and environmental” impacts including support for developing cultural heritage tourism. The rationale behind undertaking this investigation was to explore the relevance of heritage proximity in affecting tourism impacts including locals' support towards cultural heritage tourism, by employing the “triple bottom line” approach. A survey questionnaire was completed by 485 residents living at selected cultural heritage destinations in Jammu and Kashmir, India. To investigate the data, SEM was carried out. The evidence demonstrates that heritage proximity positively associated with resident perceptions of different domains of tourism impacts. Moreover, findings demonstrate that local support towards CHT results from highly favourable evaluations of the “economic, socio-cultural and environmental” impacts. The current study thus contributes towards CHT literature by highlighting the significance of heritage proximity in explaining tourism impacts and support towards CHT including necessary implications for developing CHT in the region.